Seroprevalence of neuronal antibodies in diseases mimicking autoimmune encephalitis - Mantas Vaisvilas; David Petrosian; Loreta Bagdonaite; Vera Taluntiene; Viktorija Kralikiene; Neringa Daugelaviciene; Urte Neniskyte; Gintaras Kaubrys; Natasa Giedraitiene (Scientific Reports, 2024)
Abstract Detection of neuronal antibodies for autoimmune encephalitis and paraneoplastic neurological syndromes relies on commercially available cell-based assays and lineblots. However, lineblots may reveal the presence of neuronal antibodies in patients with various non-autoimmune etiologies. Herein we describe patients with non-autoimmune etiologies (cohort B) and detectable neuronal antibodies and compare them to definite cases of autoimmune encephalitis (cohort A) for differences in clinical data. All patients positive for at least one neuronal antibody were retrospectively evaluated for autoimmune encephalitis and/or paraneoplastic neurological syndrome between 2016 and 2022. 39 cases in cohort B and 23 in cohort A were identified. In cohort B, most common diagnoses were neurodegenerative disorders in 9/39 (23.1%), brain tumors in 6/39 (15.4%) while most common detected antibodies were anti–titin (N10), anti-recoverin (N11), anti-Yo (N8) and all were detected in serum only. Differential aspects between cohort A and B were CSF pleocytosis (14/23 (60.8%) vs 11/35 (31.4%), p = 0.042, respectively), MRI features suggestive of encephalitis (6/23 (26.1%) vs 0 (0%), p = 0.002, respectively) and epilepsy restricted to temporal lobes (14/23 (60.9%) vs 2/30 (6.7%), p = 0.0003, respectively). A large proportion of lineblot results were non-specific when only serum was tested and were frequently found in non-autoimmune neurological conditions.